Glycine betaine allows enhanced induction of the Agrobacterium tumefaciens vir genes by acetosyringone at low pH. - Vernade, D (1988)
We established growth conditions for efficient induction of the vir genes of Agrobacterium tumefaciens by acetosyringone. Optimal induction was attained at a pH below 5.2 in an AB minimal medium-derived high-osmotic-strength medium containing glycine betaine. This natural osmoprotectant accelerated the adaptation of the bacteria to these conditions. We established the kinetics of induction for virB, virD, virE, and virG by using lacZ fusions, and we found that the virB mutant strain could not adapt to this low-pH medium unless 1 mM CaCl2 was added. This pH control of vir gene expression was shown to act at the level of expression of virG, which was the limiting factor. This improved vir induction at a low pH correlated with an increase in a set of proteins which was analyzed by two-dimensional gel electrophoresis. The fact that high inducibility corresponded to a reduced growth rate and the demonstration that a set of proteins was associated with the inducible state suggest that vir gene induction is linked to the adaptation of the cells to an unfavorable environment. Hence, vir gene expression in A. tumefaciens is probably dependent upon a machinery which is specific to an adaptive response; the implications for plant transformation are discussed.